Going home after infant cardiac surgery: a UK qualitative study. Issue 4 (29th January 2016) - Tregay, Jenifer; Wray, Jo; Crowe, Sonya; Knowles, Rachel; Daubeney, Piers; Franklin, Rodney; Barron, David; Hull, Sally; Barnes, Nick; Bull, Catherine; Brown, Katherine L
Abstract : Objective: To qualitatively assess the discharge processes and postdischarge care in the community for infants discharged after congenital heart interventions in the first year of life. Design: Qualitative study using semistructured interviews and Framework Analysis. Setting: UK specialist cardiac centres and the services their patients are discharged to. Subjects: Twenty-five cardiologists and nurses from tertiary centres, 11 primary and secondary health professionals and 20 parents of children who had either died after discharge or had needed emergency readmission. Results: Participants indicated that going home with an infant after cardiac intervention represents a major challenge for parents and professionals. Although there were reported examples of good care, difficulties are exacerbated by inconsistent pathways and potential loss of information between the multiple teams involved. Written documentation from tertiary centres frequently lacks crucial contact information and contains too many specialist terms. Non-tertiary professionals and parents may not hold the information required to respond appropriately when an infant deteriorates, this contributing to the stressful experience of managing these infants at home. Where they exist, the content of formal 'home monitoring pathways' varies nationally, and families can find this onerous. Conclusions: Service improvements are needed for infants going home after cardiac intervention in the UK, focusing especially on enhancing mechanisms for effective transfer of information outside the tertiary centre and processes to assist with monitoring and triage of vulnerable infants in the community by primary and secondary care professionals. At present there is no routine audit for this stage of the patient journey.